Ten-year mortality, disease progression, and treatment-related side effects in men with localised prostate cancer from the protecT randomised controlled trial according to treatment received - Neal, D; Metcalfe, C; Donovan, J; Lane, J; Davis, M; Young, G; Dutton, S; Walsh, E; Martin, R; Peters, T; Turner, E; Mason, M; et al. (Elsevier, 2019)
Background: The ProtecT trial reported intention-to-treat analysis of men with localised prostate cancer (PCa) randomly allocated to active monitoring (AM), radical prostatectomy, and external beam radiotherapy.